Viola cornuta and Viola x wittrockiana: phenolic compounds, antioxidant and neuroprotective activities on Caenorhabditis elegans - Moliner, Cristina (2018)
Different Viola species are known for their traditional use as analgesic, antitussive, febrifuge, hipnotic, analgesic and anti-inflammatory medicinal agents. Additionally, they are considered edible flowers in certain cultures. Thus, the aim of this work was to characterize the phenolic composition and to assess the neuroprotective properties of Viola cornuta and Viola x wittrockiana using in vitro and in vivo methodologies with Caenorhabditis elegans as model. The identification of the phenolic compounds was carried out with a LCDAD- ESI/MSn. The antioxidant activity of the extracts was determined in vitro using Folin- Ciocalteu, DPPH and FRAP assays and in vivo with a juglone-induced oxidative stress in C. elegans. The neuroprotective properties were evaluated measuring the ability to inhibit CNS enzymes (MAO A, AChE), and the capability to avoid paralyzing the C. elegans CL4176, an Alzheimer disease model. The phenolic content was higher in V. x wittrockiana, being quercetin-3-O-(6-O-rhamnosylglucoside)-7-O-rhamnoside the predominant compound in the extract, which also exhibited a stronger antioxidant capacity in vitro and a higher response to lethal oxidative stress on C. elegans than V. cornuta. Only V. x wittrockiana showed inhibitory effect on CNS enzymes, such as acetylcholinesterase and monoamine oxidase A, but both had protective effect against the paralysis of C. elegans. These findings suggest that the studied V. cornuta and V. x wittrockiana could be interesting candidates for age related neurodegenerative disorder associated with oxidative stress.